Pemanfaatan Platform Digital Memajukan UMKM Kerupuk Ubi di Desa Kelumpang Kecamatan GAS - Herdi Nata, M.Zul; Zayn Fuadi, Ahmad; Reyhan; Akbar, M.Rifqi; Jupita; Patmawati; Ismawardi; Desmawini; Sri Indrawati Wahyuni; Sasmita Adi Putra, Bambang (Indra Institute Research & Publication, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in sustaining local products and driving rural economic growth. This study aims to analyze the empowerment of the cassava cracker MSME in Kelumpang Village, Gaung Anak Serka District, Indragiri Hilir Regency. The assistance strategy includes brand identity creation, packaging development, business legalization, and digital marketing optimization through Shopee and TikTok Shop platforms. A case study approach was used with qualitative methods including field observation, interviews, and documentation. The findings reveal that prior to the intervention, the MSME lacked brand identity, used basic packaging, was not officially registered, and had no digital presence. Post-intervention, the MSME gained a strong brand identity, attractive packaging, legal business status, and active online sales accounts reaching markets beyond the local area. This study demonstrates that digitalization and brand strengthening significantly enhance the competitiveness of local MSMEs.